# Solve each of the

Given: 4(x + 1) + 4(1 - x) = 10 - - - - - - - (1)

Let 4x = y - - - - - - - - - - (2) substituting for y in (1)

4y2 - 10y + 4 = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 4 b = - 10 c = 4

= 4.4 = 16

And either of their sum or difference = b

= - 10

Thus the two terms are - 8 and - 2

Sum = - 8 - 2 = - 10

Product = - 8. - 2 = 16

4y2 - 10y + 4 = 0

4y2 - 8y - 2y + 4 = 0

4y(y - 2) - 2(y - 2) = 0

(y - 2) (4y - 2) = 0

(y - 2) = 0 or (4y - 2) = 0

y = 2 or y = 1/2

substituting the value of y in (2)

4x = 2 or 4x = 2 - 1

22x = 21 or 22x = 2 - 1

2x = 1 or 2x = - 1 Hence the roots of equation are Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If the roots of tMathematics - Board Papers

Find the roots ofRD Sharma - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics